The correlation between the psoriasis area severity index and ischemia-modified albumin, mean platelet volume levels in patients with psoriasis - Işık, Selda; Kılıç, Sevilay; Öğretmen, Zerrin; Çakır, Dilek Ülker; Türkön, Hakan; Cevizci, Sibel; Hiz, Meliha Merve (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Ischemia-modified albumin (IMA), a novel ischemia marker, and mean platelet volume (MPV), a determinant of platelet activation, have been reported as elevated markers in cardiovascular risk factors such as atherosclerosis, metabolic syndrome, diabetes mellitus (DM), hypertension, and dyslipidemia. As psoriasis is a chronic inflammatory disease having comorbidities, IMA and MPV can help determine the risk factors for psoriasis. Aim : To investigate the correlation between the psoriasis area severity index (PASI), IMA and MPV levels in patients with psoriasis. Material and methods: This cross-sectional, case-control study was performed between January 2014 and December 2014 at the University hospital in Çanakkale, Turkey. Forty-five patients with psoriasis and 44 healthy volunteers over 18 years of age were included in the study. In the psoriasis patient group, clinical features and PASI scores were recorded. Serum IMA and MPV concentrations were evaluated in both groups. Results: The mean IMA values were 0.85 ±0.15 and 0.79 ±0.09 (in the psoriasis patients and control groups, respectively), and there was a statistically significant difference (p = 0.048). Ischemia-modified albumin levels were not correlated with PASI scores (r = 0.024; p = 0.889) but were correlated with disease duration (r = 0.323; p = 0.048). There was no statistically significant difference between the MPV values of the two groups (8.98 ±1.14 and 9.19 ±1.28 in the psoriasis patients and control groups, respectively) (p = 0.435). Conclusions : Ischemia-modified albumin may be used as a marker for detecting oxidative stress in patients with psoriasis, especially those with a long disease duration.